A Prospective Study on Hereditary Bias of Age-Related Macular Degeneration. (March 2019) - Gabriel, Rami; Toledo-Corral, Jaime; Kenney, Maria Cristina; Mehta, Mitul
Purpose: This study employed a prospective survey to evaluate whether maternal family history or paternal family history is more likely to be found in patients with age-related macular degeneration (AMD). Methods: Family history of AMD was ascertained through a survey questionnaire of 346 patients who were confirmed by an ophthalmologist to have AMD. To compare proportions of maternally and paternally transmitted disease, the data were treated as pair matched and analyzed using the modified chi-squared McNemar test. Probands with either parent deceased before age 60 were excluded. Further analysis was conducted by grouping wet-AMD and dry-AMD patients. Results: Of the 346 surveys conducted, 91 (26.3%) reported at least 1 parent affected with AMD. Probands were 65.9% women and 44.1% men. The mean ± SD age for men was 74.3 ± 6.3 years and for women 72.7 ± 7.7 years. The average age of proband fathers was 75.0 ± 6.9 years and of proband mothers 80.1 ± 6.0 years. Probands with AMD had a higher proportion of affected mothers than fathers with an odds ratio (OR) of 3.00 and a 95% CI of 1.73 to 5.44, P = .0001. For wet AMD, the OR was 4.0 (95% CI 1.46 to 13.6) and for dry AMD, the OR was 2.6 (95% CI 1.35 to 5.4). Conclusions: Our results indicate that individuals with maternal history of AMD may be at a significantly increased risk for developing AMD than if their father had the disease. Owing to limitations in sample size and discrepancies in lifespan between sexes, further studies will be needed to generalize results. The maternal proclivity in our study sample correlates with literature describing a mitochondrial component in the disease process, soliciting further exploration into mitochondrial etiology and larger hereditary studies.